Gambling Behavior and Lotto Participation in Iceland: A Comparison before and after the Economic Collapse in 2008 - Gunnur H. Stefánsdóttir 1988- (2015)
Gambling is popular all over the world and the accessibility to gambling has become more convenient and widespread with the advent of the Internet. The main aim of this study was to examine gambling behavior on the Icelandic national lottery (Lottó 5/40), before and after the economic collapse in Iceland 2008. The purpose was also to examine the effects of the jackpot size on participants’ purchases. The current study used data from the Icelandic Lottery and Sports betting database. Participants were a total of 8,867 Icelanders who bought a Lotto ticket on the Icelandic Lottery and Sports betting website during a certain period of time. The sample contained 5,725 males (64.6%) and 3,142 females (35.4%). Results showed that there were more purchases in 2011 than in 2007, whether the jackpot was single, quadruple or sixfold. Most participants bought Lotto when the jackpot was sixfold. Moreover, it was found that males purchased more rows and tickets than females. Overall, these results underline earlier findings obtained from self-reports and suggest that economic crisis influence gambling behavior. Keywords: gambling, lotto, economic crisis, Iceland Fjárhættuspil eru vinsæl um allan heim og hefur aðgengi að þeim orðið mun útbreiddara með tilkomu Internetsins. Meginmarkmið þessarar rannsóknar var að kanna spilahegðun íslendinga í Lottó (Lottó 5/40), fyrir og eftir efnahagshrunið á Íslandi árið 2008. Markmiðið var einnig að kanna áhrif af stærð Lottópottar á kaup þátttakenda. Gögn voru fengin frá gagnabanka Íslenskrar getspár og Íslenskra getrauna. Þátttakendur voru alls 8.867 Íslendingar sem höfðu keypt sér Lottó miða á heimasíðu Íslenskrar getspár og Íslenskra getrauna á ákveðnu tímabili. Úrtakið innihélt 5.725 karla (64,6%) og 3.142 konur (35,4%). Niðurstöður sýndu að lottóspilarar keyptu fleiri raðir árið 2011 heldur en þeir gerðu árið 2007, hvort sem Lottópotturinn var einfaldur, fjórfaldur eða sexfaldur. Flestir keyptu sér Lottó miða þegar Lottópotturinn var sexfaldur. Þar að auki sýndu niðurstöðurnar að ...